Analysis of Silhouette Coefficient Evaluation with Euclidean Distance in the Clustering Method (Case Study: Number of Public Schools in Indonesia) - Dedy Hartama; Mawaddah Anjelita (Jurnal Mantik, 2022)
This study aims to find out how much the silhouette coefficient value is obtained from calculating the distance from the data to the centroid using the euclidean distance in the k-means method and to provide input in science for further research in developing the k-means method. To solve this problem, researchers use the k-means method with silhouette coefficient evaluation. Where the data source in this study took data directly from the Indonesian Central Bureau of Statistics (BPS) in the form of softcopy entitled "Statistics of Indonesia 2021" with the URL: https://www.bps.go.id. The data used in this study uses 2020 data which consists of 34 provinces. The data will be processed using the k-means method with the silhouette coefficient using the euclidean distance. The results obtained are cluster = 4 which is the best cluster for classifying the number of public schools in Indonesia by province in 2020 with a silhouette coefficient of -0.9944. By doing research, it can provide input in science for further research in developing clustering methods, especially k-means.